Impact of constitutional TET2 haploinsufficiency on molecular and clinical phenotype in humans - Eevi Kaasinen (Nature Portfolio, 2019)
Somatic heterozygous TET2 loss drives clonal hematopoiesis, which is linked to malignant cell degeneration and potentially cardiovascular disease. Here, the authors investigate the molecular impact of a germline TET2 mutation in a lymphoma family, finding elevated blood DNA methylation levels and no predisposition to atherosclerosis